V poiske zakonomernostei predsorevnovatel'noi podgotovki sportsmena - Mokeev, G. I.; Shiryaev, A. G. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
For good and desired results in competition it is necessary to have and to follow objectice regularities for training and preparation in the pre-competition training phase. Article shows what should be kept in mind in this connection.